2020
DOI: 10.1371/journal.pbio.3000740
|View full text |Cite
|
Sign up to set email alerts
|

A single touch can provide sufficient mechanical stimulation to trigger Venus flytrap closure

Abstract: The carnivorous Venus flytrap catches prey by an ingenious snapping mechanism. Based on work over nearly 200 years, it has become generally accepted that two touches of the trap's sensory hairs within 30 s, each one generating an action potential, are required to trigger closure of the trap. We developed an electromechanical model, which, however, suggests that under certain circumstances one touch is sufficient to generate two action potentials. Using a force-sensing microrobotic system, we precisely quantifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“… 30 , 31 The Venus flytrap uses the distinct electrical states of its cells to process information, 29 and this mechanism could allow for reacting to a wide range of prey movements. 32 Also, it has been observed that the Venus flytrap has several interconnected electrical circuits. 28 Despite these interesting features, this plant is not an oddity.…”
Section: Plant Behaviors and The Mechanisms Of Electrical Signalsmentioning
confidence: 99%
“… 30 , 31 The Venus flytrap uses the distinct electrical states of its cells to process information, 29 and this mechanism could allow for reacting to a wide range of prey movements. 32 Also, it has been observed that the Venus flytrap has several interconnected electrical circuits. 28 Despite these interesting features, this plant is not an oddity.…”
Section: Plant Behaviors and The Mechanisms Of Electrical Signalsmentioning
confidence: 99%
“…The different aspects of mechanotransduction in the Venus flytrap were investigated through various theoretical and experimental approaches. Previously, we introduced an electromechanical model [ 10 ] built on the concepts of plant electrical memory [ 4 ] to complement our force-deflection tests on sensory hairs. We found hair deflection thresholds for angular displacement and velocity which successfully elicit action potentials, thereby closing the trap.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical tests on sensory hairs were able to quantify the stimulus thresholds needed to elicit action potentials (APs) and, furthermore, a loss of sensitivity at high stimulation frequencies was reported [ 9 ]. Recently, with the help of an electromechanical model, it was shown that a charge-dependent rule can explain mechanotransduction in the flytrap’s sensory hair [ 10 ]. Subsequent experiments confirmed that the number of stimulations needed to close the trap depends on the stimulus parameters, namely the angular velocity and the angular displacement of the sensory hair.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the lobes receive two or more successive stimuli within approximately 30 seconds, they suddenly snap shut and trap the prey inside (Brown and Sharp 1910 ). A recent study employing the fine displacement of the sensory hair showed that a single deflection with relatively slow angular velocity (0.03–4 radian per second) can induce multiple action potentials and thus trigger the trap closure (Burri et al 2020 ). Live-imaging analysis using transgenic D. muscipula has recently demonstrated that cytosolic Ca 2+ levels in the trap lobes cumulatively increase in response to individual stimuli, suggesting that Ca 2+ plays a role in this counting system (Suda et al 2020 ).…”
Section: Movements Of Carnivorous Plants: Beyond the Upper Limit Of Wmentioning
confidence: 99%